2004
DOI: 10.1002/ps.972
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, crystal structure and herbicidal activity of mimics of intermediates of the KARI reaction

Abstract: Two mimics of the intermediate in the reaction catalyzed by ketol-acid reductoisomerase (KARI) were synthesized. Their structures were established on the basis of elemental analyses, IR, 1H NMR and GC/mass detector. The crystal structure of compound 2 was found to be a substituted dioxane, formed by the condensation of two molecules. The two compounds showed some herbicidal activity on the basis of tests using rape root and barnyard grass growth inhibition. However, the herbicidal effect was weaker in greenhou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 15 publications
0
51
0
Order By: Relevance
“…Table 2 showed that the trifluoromethylated ones (8) have some herbicide activity against monocotyledonous Echinochloa crus-galli L. Beauv (barnyard grass), which was valued by using the reported procedure (the inhibition of the seeding growth of barnyard grass) [39,40]. Due to the continuing evolution of herbicide resistance in agriculture, discovery of new herbicides such as potent barnyard grass inhibitors is important to widen its structural diversity that might possess new mode of action and then lack resistance to the currently used chemicals [41,42].…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 showed that the trifluoromethylated ones (8) have some herbicide activity against monocotyledonous Echinochloa crus-galli L. Beauv (barnyard grass), which was valued by using the reported procedure (the inhibition of the seeding growth of barnyard grass) [39,40]. Due to the continuing evolution of herbicide resistance in agriculture, discovery of new herbicides such as potent barnyard grass inhibitors is important to widen its structural diversity that might possess new mode of action and then lack resistance to the currently used chemicals [41,42].…”
Section: Resultsmentioning
confidence: 99%
“…The title compounds were screened for herbicidal activity against B. campestris and E. crus-galli using a previously reported procedure [20,21], and the data of herbicidal activity were listed in Table 1. It was found that the title compounds are well tolerated in two weeds during the bioassay procedure.…”
Section: Resultsmentioning
confidence: 99%
“…[49][50][51]. The results showed that the six isomers exhibited obvious difference in herbicidal activity.…”
Section: Biological Activitymentioning
confidence: 88%